Letter to Jane Tolmach from A. Dan Reilly, Chairman of California State Legislative Board United Transporation Union - A. Dan Reilly:::::: (1976)
In a May 24, 1976 letter, A. Dan Reilly of the California State Legislative Board of the United Transportation Union (AFL-CIO) confirmed Jane Tolmach's endorsement for the June primary. The union enclosed a $500 contribution to assist her campaign, noting it could not be used for any federal candidate. The letter conveyed best wishes for success in the primary election.